A low-cost solar disinfection platform: hydrogel-encapsulated benzyl frameworks for continuous in situ H2O2-driven water treatment - Wenjuan Zhang; Lizheng Chen; Xiaojuan Zhao; Shiling Zhang; Chongling Cheng; Juan Du; Kaikai Ba; Bo Wang; Tengfeng Xie; Xuefeng Chu; Gang Liu; Dayang Wang (Water Research, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Enantioselective metabolic mechanism and metabolism pathway of tetraconazole in human liver microsomes: In vitro and in silico study - Shiling Liu; Junqi Zhu; Yu Wang; Wenyu Dai; Ya Zhou; Tengfei Zhang; Xianzhang Yang; Jingjing Wu; Yanmei Liu; Jie Luo; Huihua Tan; Feng Zhao (Environmental Pollution, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Greenness extraction, purification, and hypolipidemic activities of alisol B from Alismatis Rhizoma - Tao Gao; Zonghua Zhao; Zhihao Duan; Shiling Feng; Zizhong Tang; Ming Yuan (Food Bioscience, 2025)

The xylem anatomical structure, physiological characteristics and aromatic components analyses explain the difference of fungal solution induced agarwood formation in Aquilaria sinensis - Shengjiang Pang; Weiwei Zhao; Guihua Huang; Qingbin Jiang; Zaizhi Zhou; Qingqing Zhang; Zuwei Tian; Pei Zhang; Zhongguo Li; Shuokun Deng; Shiling Liu; Baoguo Yang (Trees, 2025)

Co-adjustment of chitosan-based film structure by pH and anthocyanin concentration for the development of reshness-indicating labels on chilled mutton - Mou Zhao; Huanhuan Yang; Cenchen Ran; Ziyi Liao; Zihang Zhai; Jingtao Sun; Shiling Lu; Hua Ji; Juan Dong (Food Chemistry, 2025)

Effects of Continuous Grafting on the Growth and Selenium Accumulation Characteristics in the Post-Generations of Tomato - Shiling Meng; Xiaoli Song; Wende Zhou; Juan Huang; Yatian Zhao; Wanjia Tang; Yi Tang; Bo Sun; Huanxiu Li; Zhi Huang (Journal of Soil Science and Plant Nutrition, 2025)

Characterization of ultrasound-induced soybean peptide particles (SPPs) and SPP-stabilized Pickering emulsions combined with amino acid sequence analysis - Ping Han; Mou Zhao; Zhouping Wang; Nengmao Chen; Fuguo Liu; Shiling Lu; Juan Dong; Jingtao Sun (Food Hydrocolloids, 2025)

Correcting microplastic pollution and risk assessment in Chinese watersheds - Feng Yu; Weiwei Yu; Yan Zhao; Yue Liang; Jiang Hu; Rongqi Liu; Shiling Chen; Qinwei Chen; Yuanxin Liu; Xiyin Zheng; Xinyan Li (Environmental Pollution, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Basing target enzyme study the enantioselective bioactivity action mechanism of flusulfinam, a novel HPPD inhibitor herbicide - Shiling Liu; Siying Qin; Tengfei Zhang; Heng Zhang; Junqi Zhu; Xiaoli Li; Yuanfu Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2025)

Novel anti-oxidative peptides from equine hemoplasma protein hydrolysates: Purification, identification and protective effects on Caco-2 cells - Zehao Ma; Yuhan Li; Ziqiao Zhao; QianQian Song; Qingling Wang; Shiling Lu; Jingyun Wang (Food Research International, 2025)

Gel properties of sheep's hoof gelatin-dietary polysaccharide interpenetrating polymer network complex gels with application in low fat lamb patties - Yuhan Li; Hongyan Yu; Ziqiao Zhao; Qianqian Song; Zehao Ma; Jingyun Wang; Shiling Lu; Qingling Wang (Food Chemistry, 2025)

Synergistic catalysis of dual-sites promoted cycloaddition of CO2 with epoxides - Shiling Zhao; Kaizhi Wang; Beibei Yang; Zehui Sun; Yu Zhao (Fuel, 2025)

Effects of glycation modifications of different glycosylating agents on the molecular structure and gel properties of sheep's hoof gelatin - Yuhan Li; Nanqi Li; Qianqian Song; Ziqiao Zhao; Ruyan Yuan; Jingyun Wang; Shiling Lu; Qingling Wang (Food Hydrocolloids, 2025)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Effects of Mutual Grafting on Fruit Quality in Post-grafting generation of Two Genotypes Cherry Tomato (Lycopersicon esculentum) - Zhi Huang; Shiling Meng; Huizhong Luo; Wende Zhou; Juan Huang; Yatian Zhao; Xiaoli Song; Yi Tang; Bo Sun; Huanxiu Li (Journal of Soil Science and Plant Nutrition, 2024)

Selective hydrogenation of biphenyl to cyclohexylbenzene over Cu based catalysts - Shiling Zhao; Kaizhi Wang; Beibei Yang; Yu Zhao; Jingxuan Cai (Chemical Engineering Journal, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Assessing the structural and foaming property changes in egg yolk proteins due to malondialdehyde: Experimental and molecular docking studies - Jingya Chen; Jiaxin Jin; Yu Liu; Mengbin Zhao; Zeliang Qi; Wenjing Shi; Yangyang Li; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Engineering heterogeneous hierarchical hydrogels based on Artemisia sphaerocephala Krasch polysaccharide/whey protein isolate fibrils aqueous two-phase emulsion - Pan Zhang; Qingxia Gou; Shiling Zhang; Xinyue Mei; Xu Zhao; Guoliang Li; Yapeng Fang; Mouming Zhao; Katsuyoshi Nishinari; Xiaolin Yao (Food Hydrocolloids, 2024)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Biodegradation characteristics and mechanism of terbuthylazine by the newly isolated Agrobacterium rhizogenes strain AT13 - Yanmei Liu; Wei Liu; Menghao Li; Shiling Liu; Dingjiao Peng; Feng Zhao; Xiaogang Wu; Huihua Tan (Journal of Hazardous Materials, 2023)